The Epidemiology of COVID-19 in the Gansu and Jinlin Provinces, China - Fan, Jingchun; Hambly, Brett D.; Bao, Shisan (Frontiers in Public Health, 2020)
The COVID-19 outbreak has become a pandemic. The outbreak was able to be controlled in China by mid-April through the implementation of critical measures, however, significant reverse transmission has resulted in hot spots perturbing prevention and control. To date, there have only been a total of 92 indigenous COVID-19 cases confirmed in the Gansu Province, which is considered to be a consequence of the strict screening approach applied during the outbreak. The emergency response level to COVID-19 were able to be decreased from high to low, despite some relatively minor reverse transmission cases from other countries in March 2020. The stringent preparative measures undertaken by the Gansu authorities, involving high level, streamlined cooperation between the transportation, quarantine and medical resource departments have underpinned this success. There has been an emergence of clusters of freshly infected COVID-19 patients in the Jilin Province in northeast China. The single largest cluster has been in Shulan of the Jilin Province, involving 43 confirmed infections. A strict lockdown was implemented immediately. The source of the current outbreak of COVID-19 is suggested to be travellers returning from Russia. The current strategy from the Chinese authorities is aimed at preventing reverse transmission via international importation, to avert a rebound of COVID-19 in China. These data highlight the need for an exceptionally high level of vigilance and for a pre-emptive response, that is informative for the development of policy to prevent a second and further waves of infections in general.